2019
DOI: 10.1021/jacs.9b10329
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Resistive-Pulse Sensing

Abstract: Resistive-pulse sensing with biological or solid-state nanopores and nanopipettes has been widely employed in detecting single molecules and nanoparticles. The analytical signal in such experiments is the change in ionic current caused by the molecule/particle translocation through the pipet orifice. This paper describes a new version of the resistive-pulse technique based on the use of carbon nanopipettes (CNP). The measured current is produced by electrochemical oxidation/reduction of redox molecules at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
108
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 43 publications
(73 reference statements)
6
108
0
Order By: Relevance
“…This short review evidenced that the ability of monitoring and quantifying intracellular timedependent fluxes and concentrations of ROS & RNS with Types-I & II nanoelectrodes has already enabled scrutinizing important biological phenomena that would have remained speculative or poorly understood without proper analytical tools offering a sufficient chemical, kinetic and spatial resolution. It is certain that many further interesting developments will occur upon adapting these approaches to include resistive-pulse sensing functionalities [51,52], or when combining them with stretchable electrodes to investigate the nature of causal relationships between intracellular redox status and signaling.…”
Section: Resultsmentioning
confidence: 99%
“…This short review evidenced that the ability of monitoring and quantifying intracellular timedependent fluxes and concentrations of ROS & RNS with Types-I & II nanoelectrodes has already enabled scrutinizing important biological phenomena that would have remained speculative or poorly understood without proper analytical tools offering a sufficient chemical, kinetic and spatial resolution. It is certain that many further interesting developments will occur upon adapting these approaches to include resistive-pulse sensing functionalities [51,52], or when combining them with stretchable electrodes to investigate the nature of causal relationships between intracellular redox status and signaling.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Pan et al showed that translocation of single liposomes and release of loaded dopamine can be monitored simultaneously using open carbon nanopipettes (CNPs). 14 …”
mentioning
confidence: 99%
“…(Additional amperometric traces of CNPs are shown in Figure S2 ). It should be noted that this approach is different from electrochemical resistive-pulse sensing, 14 as no redox mediator is added in the suspension of vesicles and the vesicle sizes are grouped by the use of different pipette tip sizes instead. Important information about the release event can be obtained by analyzing the individual spikes.…”
mentioning
confidence: 99%
“…Resistive-pulse sensing of liposomes 49 and intracellular biological vesicles 28 with carbon CNPs was reported recently. Similar to quartz pipettes, the translocation of negatively charged liposomes through a oating carbon CNP was found to be driven by electroosmosis.…”
Section: +mentioning
confidence: 99%
“…Important advantages of conductive pipettes for nanopore sensing (tunable surface charge and potential) and nanoelectrode applications (a small physical size and a signicant conductive surface area) are discussed below along with a recently developed combination of resistive-pulse sensing with nanoelectrochemistry. 49…”
Section: Introductionmentioning
confidence: 99%